2002
DOI: 10.1088/0022-3727/36/2/307
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a friction-based self-consistent multicomponent diffusion model in Plasimo

Abstract: In order to improve the realism of our Plasimo computer model [1,2] in modelling multi-ion mixtures, we developed and implemented a self-consistent multicomponent diffusion model based on frictions. As presented, this diffusion model includes effects of the ambipolar electric field as well as any external electric fields. Moreover, it is comparatively easy to include other diffusion contributions. This model was shown to produce good and consistent results for both single and multi-ion mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Therefore, Equation (A39) can be applied in the developed QN model. In case of a complex mixture and electronegative plasmas, another method is needed …”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Equation (A39) can be applied in the developed QN model. In case of a complex mixture and electronegative plasmas, another method is needed …”
Section: Appendixmentioning
confidence: 99%
“…In case of a complex mixture and electronegative plasmas, another method is needed. [83] Diffusion of Neutral Particles, Fick's Model…”
Section: Ambipolar Diffusion Approximation For Charged Particlesmentioning
confidence: 99%
“…The results are valid for non-magnetized plasma and have been used to simulate the cascaded arc plasma [24,25]. A few years later, Hartgers developed an alternative, equivalent formulation of the problem that was based on the concept of friction, rather than diffusion [77]. While equivalent, the look and feel of these formulations is quite different.…”
Section: Diffusion In Two-temperature Plasmasmentioning
confidence: 99%
“…In this paper, we will derive a transport equation that describes elemental transport. It will have a structure identical to the general φ-equation (3), where φ represents something that can be interpreted as the partial pressure of an element, and where c φ and λ φ are the corresponding 'velocity' and 'diffusion' coefficients. Naturally, it will be shown that S φ = 0, since elements cannot be created or destroyed.…”
Section: Theorymentioning
confidence: 99%